Analisis Antrian Di Stasiun Tugu Yogyakarta - Handoko, Handoko; Astuti, Septiana Widi (Politeknik Perkeretaapian Indonesia Madiun, 2017)
Queue is a common situation that is common in everyday life where consumers wait in front of the counter to get a turn of service or service facilities. The study aims to determine the performance of the queuing system at the train ticket counter at Yogyakarta Tugu Station. This research is an action research. The population in this study are all customers who come to Yogyakarta Tugu Railway Station to purchase train tickets. Sampling using accidental sampling technique. Data collection techniques used are the method of observation and documentation. Data analysis techniques used queuing formulas for Model B: M / M / S. The results showed that the performance of the queuing system at the train ticket counter at Yogyakarta Tugu Station was not optimal.